Knowledge and Practice of Health Care Workers regarding Needle Stick Injuries in a Tertiary Care Center of Nepal - Singh, B.; Paudel, B.; KC, S. (Kathmandu University Medical Journal, 2017)
Background Needle stick injuries are common health hazards among health care workers. Considering the increasing prevalence of body fluid borne infectious diseases; knowledge regarding the common errors and universal precautions are vital for the prevention of such accidents.Objective This study aimed to assess for knowledge and practice approaches among health care workers regarding needle stick injuries.Method This is a cross sectional survey was conducted using an anonymous, self-reporting 25-item structured questionnaire at a tertiary care center of central Nepal. A total of 165 health care personnel of working experience of more than 6 months were included in the study. Questionnaire included aspects of prevalence and knowledge on needle stick injury, hepatitis B immunization status and post exposure prophylaxis for HIV.Result Prevalence of needle stick injury was found to be 703 per 1000 health care worker (70.3%) during their working tenure and majority of the injury happened among nurses (p